Optimising Administrative Employees’ Productivity in XYZ District of Sarawak: The Role of Physical Workspace Environments - Maslan, Nurul Masturina; Anis, Azilah; Islam, Rafikul (Information Management and Business Review, 2024)
A pleasant physical working environment is essential to prevent unnecessary stress among administrative employees. This is because administrative employees spend most of their working hours within a building or a physical workspace environment. With these routine tasks and the extensive time spent in the workspace, discomfort can easily arise in their productivity and performance. Therefore, this study aims to identify the impact of the physical workspace environment on administrative employees’ productivity at XYZ district, Sarawak, by employing four dimensions of the physical workspace environment: temperature, noise level, lighting, and color. This study employs a quantitative methodology, and questionnaires were used to collect the data by utilizing the e-survey. The data was gathered from 81 administrative employees via convenience sampling from private and public organizations located in XYZ district, Sarawak, and analyzed using reliability analysis, descriptive analysis, correlation analysis, and multiple regression analysis. The findings indicate that this study’s four dimensions of the physical workspace environment, i.e., temperature, noise level, lighting, and color, have a significant relationship with administrative employees’ productivity in XYZ district, Sarawak. The study concludes that organizations can significantly boost the productivity and performance of administrative employees by optimizing the physical workspace environment. It also suggests that organizations should not only aim to create a conducive workspace but also consider the preferences and well-being of their employees. This research contributes to a better understanding of the environmental factors affecting employee productivity and offers practical insights for organizational improvement in physical workspace design.